Tryptophan Biosynthesis in Cell Cultures of Nicotiana tabacum - Delmer, Deborah P. (1968)
Some of the general features of the pathway for l-tryptophan biosynthesis in cell cultures of Nicotiana tabccum var. Wisc. 38 have been investigated. The results of both isotope competition and direct-labeling experiments show that shikimic acid, anthranilic acid, indoleglycerol phosphate, and indole can serve as precursors to l-tryptophan in these cells, indicating that, in terms of its biochemical intermediates, the pathway is similar to that described for the bacteria and fungi.